2023
DOI: 10.1021/jacs.3c06262
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Catalyst-Free Ester Metathesis Reaction for Covalent Adaptable Networks

Shijia Yang,
Wenxing Liu,
Jing Guo
et al.

Abstract: Thermosetting polymers possess excellent environmental resistance and mechanical properties but cannot be reprocessed due to their covalently cross-linked structures. Recycling of thermosets via the implantation of dynamic covalent bonds offers a promising solution. Here, we report the direct and catalyst-free ester metathesis of N-acyloxyphthalimide (NAPI) at about 100 °C without the requirement of hydroxyl groups and its utilization for the fabrication of covalent adaptable networks (CANs). NAPI metathesis h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…This is attributed to the diselenide bond's ability to be reversibly broken and reformed under visible light. Such a 173 While the reaction appears similar to traditional transesterification on the surface, the study revealed that the actual mechanism is a radical reaction involving the homolysis of the C−O bond. 3.2.1.1.5.…”
Section: Other Addition Reactionsmentioning
confidence: 82%
See 1 more Smart Citation
“…This is attributed to the diselenide bond's ability to be reversibly broken and reformed under visible light. Such a 173 While the reaction appears similar to traditional transesterification on the surface, the study revealed that the actual mechanism is a radical reaction involving the homolysis of the C−O bond. 3.2.1.1.5.…”
Section: Other Addition Reactionsmentioning
confidence: 82%
“…Another notable dynamic bond is the C–O bond found in N -acyloxyphthalimide. In a recent study, Zhao and Xu et al introduced a method to synthesize reprocessable covalent network polymers using a catalyst-free transesterification of N -acyloxyphthalimide . While the reaction appears similar to traditional transesterification on the surface, the study revealed that the actual mechanism is a radical reaction involving the homolysis of the C–O bond.…”
Section: Reprocessable Covalent Network Polymers Enabled By Dcvcmentioning
confidence: 99%
“…Especially in the case of maleic-graed polyolens, the ester linkages formed with GL provide a means for transesterication or ester thesis during melt processing, allowing the material to behave macroscopically as a thermoplastic despite forming covalent bonds between the particles and matrix. 6,50…”
Section: Closed-loop Recyclability Of Gl Blendsmentioning
confidence: 99%
“…Due to the three-dimensionally cross-linked structures, thermosets generally provide high strength and stiffness, structural stability, and resistance to abrasion and solvents, playing irreplaceable roles in many fields such as electronic packaging, coatings, adhesives, additive manufacturing, and composites. Nevertheless, thermosets cannot be recycled after their initial formation owing to the permanent covalent cross-links, leading to increasing plastic wastes and environmental pollution. An elegant strategy to turn cross-linked polymer networks into recyclable plastics is to replace the covalent cross-links by dynamic covalent bonds, giving rise to the formation of dynamic covalent thermosets. Dynamic covalent bonds are usually dormant at ambient conditions but capable of dynamically exchanging under stimuli (e.g., heat, light, pH). Hence, dynamic covalent thermosets behave like traditional thermosets at ambient conditions but display thermoplastic properties under stimuli, endowing the dynamic covalent thermosets with recyclability. However, similar to the traditional thermosets, dynamic covalent thermosets always suffer from the unfavorable trade-off between their strength/stiffness and ductility/toughness. Those with high tensile strength (e.g., >40 MPa) and Young’s moduli (e.g., >1.0 GPa) are generally fragile because of the very low elongation at break (<10% in most cases), whereas the highly ductile ones generally exhibit relatively low tensile strength and Young’s moduli. , This is because the mechanical strength/stiffness can be effectively enhanced by increasing the dynamic covalent cross-linking degree, which however naturally suppresses the polymer chain mobility and extensibility, leading to decreased ductility and toughness. , Therefore, there is a significant need to reconcile the trade-off between strength/stiffness and ductility/toughness of dynamic covalent thermosets to expand their practical utility.…”
Section: Introductionmentioning
confidence: 99%